Sperm acquire epididymis-derived proteins through epididymosomes. Issue 4 (5th February 2022) - Barrachina, F; Battistone, M A; Castillo, J; Mallofré, C; Jodar, M; Breton, S; Oliva, R
Abstract: STUDY QUESTION: Are epididymosomes implicated in protein transfer from the epididymis to spermatozoa? SUMMARY ANSWER: We characterized the contribution of epididymal secretions to the sperm proteome and demonstrated that sperm acquire epididymal proteins through epididymosomes. WHAT IS KNOWN ALREADY: Testicular sperm are immature cells unable to fertilize an oocyte. After leaving the testis, sperm transit along the epididymis to acquire motility and fertilizing abilities. It is well known that marked changes in the sperm proteome profile occur during epididymal maturation. Since the sperm is a transcriptional and translational inert cell, previous studies have shown that sperm incorporate proteins, RNA and lipids from extracellular vesicles (EVs), released by epithelial cells lining the male reproductive tract. STUDY DESIGN, SIZE, DURATION: We examined the contribution of the epididymis to the post-testicular maturation of spermatozoa, via the production of EVs named epididymosomes, released by epididymal epithelial cells. An integrative analysis using both human and mouse data was performed to identify sperm proteins with a potential epididymis-derived origin. Testes and epididymides from adult humans (n = 9) and adult mice (n = 3) were used to experimentally validate the tissue localization of four selected proteins using high-resolution confocal microscopy. Mouse epididymal sperm were co-incubated with carboxyfluorescein succinimidyl ester (CFSE)-labeled epididymosomes (n = 4 mice), and visualized using high-resolution confocal microscopy. PARTICIPANTS/MATERIALS, SETTING, METHODS: Adult (12-week-old) C57BL/CBAF1 wild-type male mice and adult humans were used for validation purposes. Testes and epididymides from both mice and humans were obtained and processed for immunofluorescence. Mouse epididymal sperm and mouse epididymosomes were obtained from the epididymal cauda segment. Fluorescent epididymosomes were obtained after labeling the epididymal vesicles with CFSE dye followed by epididymosome isolation using a density cushion. Immunofluorescence was performed following co-incubation of sperm with epididymosomes in vitro . High-resolution confocal microscopy and 3D image reconstruction were used to visualize protein localization and sperm-epididymosomes interactions. MAIN RESULTS AND THE ROLE OF CHANCE: Through in silico analysis, we first identified 25 sperm proteins with a putative epididymal origin that were conserved in both human and mouse spermatozoa. From those, the epididymal origin of four sperm proteins (SLC27A2, EDDM3B, KRT19 and WFDC8) was validated by high-resolution confocal microscopy. SLC27A2, EDDM3B, KRT19 and WFDC8 were all detected in epithelial cells lining the human and mouse epididymis, and absent from human and mouse seminiferous tubules. We found region-specific expression patterns of these proteins throughout the mouse epididymides. In addition, while EDDM3B, KRT19 and WFDC8 were detected in both epididymal principal and clear cells (CCs), SLC27A2 was exclusively expressed in CCs. Finally, we showed that CFSE-fluorescently labeled epididymosomes interact with sperm in vitro and about 12–36% of the epididymosomes contain the targeted sperm proteins with an epididymal origin. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: The human and mouse sample size was limited and our results were descriptive. The analyses of epididymal sperm and epididymosomes were solely performed in the mouse model due to the difficulties in obtaining epididymal luminal fluid human samples. Alternatively, human ejaculated sperm and seminal EVs could not be used because ejaculated sperm have already contacted with the fluids secreted by the male accessory sex glands, and seminal EVs contain other EVs in addition to epididymosomes, such as the abundant prostate-derived EVs. WIDER IMPLICATIONS OF THE FINDINGS: Our findings indicate that epididymosomes are capable of providing spermatozoa with a new set of epididymis-derived proteins that could modulate the sperm proteome and, subsequently, participate in the post-testicular maturation of sperm cells. Additionally, our data provide further evidence of the novel role of epididymal CCs in epididymosome production. Identifying mechanisms by which sperm mature to acquire their fertilization potential would, ultimately, lead to a better understanding of male reproductive health and may help to identify potential therapeutic strategies to improve male infertility. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Spanish Ministry of Economy and Competitiveness (Ministerio de Economía y Competividad; fondos FEDER 'una manera de hacer Europa' PI13/00699 and PI16/00346 to R.O.; and Sara Borrell Postdoctoral Fellowship, Acción Estratégica en Salud, CD17/00109 to J.C.), by National Institutes of Health (grants HD040793 and HD069623 to S.B., grant HD104672-01 to M.A.B.), by the Spanish Ministry of Education, Culture and Sports (Ministerio de Educación, Cultura y Deporte para la Formación de Profesorado Universitario, FPU15/02306 to F.B.), by a Lalor Foundation Fellowship (to F.B. and M.A.B.), by the Government of Catalonia (Generalitat de Catalunya, pla estratègic de recerca i innovació en salut, PERIS 2016-2020, SLT002/16/00337 to M.J.), by Fundació Universitària Agustí Pedro i Pons (to F.B.), and by the American Society for Biochemistry and Molecular Biology (PROLAB Award from ASBMB/IUBMB/PABMB to F.B.). Confocal microscopy and transmission electron microscopy was performed in the Microscopy Core facility of the Massachusetts General Hospital (MGH) Center for Systems Biology/Program in Membrane Biology which receives support from Boston Area Diabetes and Endocrinology Research Center (BADERC) award DK57521 and Center for the Study of Inflammatory Bowel Disease grant DK43351. The Zeiss LSM800 microscope was acquired using an NIH Shared Instrumentation Grant S10-OD-021577-01. The authors have no conflicts of interest to declare.